REVITALISASI PENDEKATAN BIOPHILIC DAN PEMISAHAN SIRKULASI RAMAH PENGGUNA DI DESA SIRNAGALIH - Rahayu, Sri; Hantari, Anjas Ninda; Trisetia Ningsi , Salwa; Safira, Risma; Irawan, Adelia Putri; Fadhillah, Fitra Agung; Saepuloh, Eep; Nhatasya, Dita; Haikal, Fikri; Adika, Helmi; Tiara Eka Putri, Vidya; Kamil Agustina, Aisha; Surya Prana, Bambang; Axel Kurnia R , Gian; Faturohman, Juan; Revin Febrian, Moch; Mohammad P, Aldi Lulu; Putra, Rifama; Febrian, Azis; Nugraha, Arief Prasetya; Muhammad Fathir, Reyhan; Aditia Heryadi, Muhammad; Ihsan, Faiq Fadhali; Marudi, Naufal Kalam (Institut Teknologi Garut, 2025)
Sirnagalih Village Park is a public green open space with ecological, social, educational, and aesthetic functions. However, its existing condition is less than optimal due to minimal shade vegetation, the dominance of hard surfaces, the lack of separation between pedestrian and vehicle circulation, and a weak local identity. This study aims to redesign the park through a biophilic design approach and user-friendly circulation separation to create a safe, comfortable, and inclusive public space. The research method uses a case study with a qualitative descriptive approach through literature studies, field observations, interviews with village officials, data analysis, and the preparation and evaluation of design concepts through FGDs. The design results show that the application of biophilic design through elements of vegetation, water, natural materials, and spatial patterns improves thermal comfort, ecological quality, and a more integrated spatial experience with nature. Separation of circulation through elevation differences, gentle ramps, and vegetation barriers improves safety and accessibility for all users. The spatial zoning is divided into ecological, productive, and aesthetic zones to support ecological and educational functions and strengthen local identity. Thus, this revitalization produces an environmentally friendly, functional, and sustainable village park, while strengthening the character of Sirnagalih Village.